Means of mass information and destabilization of society: the aspects of interrelation - Postalovsky, Alexander V. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to the sociological analysis of the role of mass media in the processes of destabilization of sociopolitical systems on the example of the study of the conflict-prone field of the post-Soviet space. The questions of formation in the sociological theory of the concept of destabilization, which complements the classical theory of revolution, based primarily on the mandatory determination of the revolutionary process of economic factors. Hypothesis C. Huntington is empirically tested. on the hypothesis of value orientations and cultural differences as sources of invariant forms of conflict in modern conditions of society.
Keywords: mass media; transformation; destabilization; values; revolution